Pemberdayaan Masyarakat Melalui Pengembangan Bisnis Dengan Pemanfaatan Sampah - Muhammad Mudzakkir; Anthonius Prahendratno; Dendi Afrizal; Neneng Mulyaningsih; Devi wardiyanti (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
Waste is a common problem in the community. Especially in the Kebonratu village community. The lack of education about business development using waste in Kebonratu Village has made people indifferent to the waste in the environment. Where the existence of waste management activities can become a selling point that benefits the community itself. And another benefit of community empowerment through business development by utilizing waste is that most of the waste comes from household waste, which can reduce the volume of waste which has the potential to cause slums and environmental pollution which causes the environment to become unhealthy and dirty. Based on the results of interviews with the Kebonratu village head, there are several community problems related to the waste problem, meaning the lack of public education regarding business development using waste. Waste management through recycling activities to reuse organic waste so that it has selling value.